Bioinspired Multifunctional Black Phosphorus Hydrogel with Antibacterial and Antioxidant Properties: A Stepwise Countermeasure for Diabetic Skin Wound Healing. Issue 12 (25th March 2022) - Ding, Qiuyue; Sun, Tingfang; Su, Weijie; Jing, Xirui; Ye, Bing; Su, Yanlin; Zeng, Lian; Qu, Yanzhen; Yang, Xu; Wu, Yuzhou; Luo, Zhiqiang; Guo, Xiaodong
Abstract: Cutaneous wound healing, especially diabetic wound healing, is a common clinical challenge. Reactive oxygen species (ROS) and bacterial infection are two major detrimental states that induce oxidative stress and inflammatory responses and impede angiogenesis and wound healing. A derivative of the metabolite itaconate, 4‐octyl itaconate (4OI) has attracted increasing research interest in recent years due to its antioxidant and anti‐inflammatory properties. In this study, 4OI‐modified black phosphorus (BP) nanosheets are incorporated into a photosensitive, multifunctional gelatin methacrylamide hydrogel to produce a new photothermal therapy (PTT) and photodynamic therapy (PDT) system with antibacterial and antioxidant properties for diabetic wound regeneration. Under laser irradiation, the 4OI–BP‐entrapped hydrogel enables rapid gelation, forming a membrane on wounds, and offers high PTT and PDT efficacy to eliminate bacterial infection. Without laser irradiation, BP acts as a carrier and controls the release of 4OI, with which it synergistically enhances antioxidant activity, thus alleviating excessive ROS damage to endothelial cells, promoting neovascularization, and facilitating faster diabetic wound closure. These findings indicate that 4OI–BP‐entrapped multifunctional hydrogel provides a stepwise countermeasure with antibacterial and antioxidant properties for enhanced diabetic wound healing and may lead to novel therapeutic interventions for diabetic ulcers. Abstract : An injectable, antibacterial, and antioxidant effects hydrogel is explored as a delivery platform to treat diabetic foot ulcers. The hydrogel can exert antibacterial effects by photothermal and photodynamic properties under near‐infrared irradiation. It functions as a carrier of 4OI and controls its release to ameliorate oxidative stress and promote wound healing.